Traveller's Palm, Botanical Gardens, Trinidad - (:unkn) unknown (Davidson and Todd Ltd., Trinidad, 2010)
The postcard shows a man standing next to a Traveller's Palm located in the Botanical Gardens, Trinidad.
Colour: Sepia (print); Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Botanical gardens; Ravenala madagascariensis; Plants; Trees--Traveller's Palm